2004
DOI: 10.1677/joe.1.05873
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-I signaling is modified during chondrocyte differentiation

Abstract: Insulin-like growth factor-I (IGF-I) is a critical regulator of skeletal growth. While IGF-I has been shown to be a potent chondrocyte mitogen in vitro, its role in chondrocyte differentiation is less well characterized. We chose to study the action of IGF-I on an accepted model of chondrocyte differentiation, the ATDC5 cell line. Insulin concentrations sufficiently high to interact with the IGF-I receptor are routinely used to induce ATDC5 cells to differentiate. Therefore, we first examined the ability of IG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
48
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 33 publications
10
48
0
Order By: Relevance
“…5C). These data are in agreement with the findings of Phornphutkul et al (2004) who observed minimal ERK response to IGF-I in hypertrophic ATDC5 cells, but the functional role of other IGF-related signaling pathways were not studied by these investigators. Taken together, these data indicate that the MAPK/ERK1/2 pathway is being inactivated both during spontaneous and IGF-Imediated early differentiation of RCJ cells.…”
Section: Discussionsupporting
confidence: 91%
“…5C). These data are in agreement with the findings of Phornphutkul et al (2004) who observed minimal ERK response to IGF-I in hypertrophic ATDC5 cells, but the functional role of other IGF-related signaling pathways were not studied by these investigators. Taken together, these data indicate that the MAPK/ERK1/2 pathway is being inactivated both during spontaneous and IGF-Imediated early differentiation of RCJ cells.…”
Section: Discussionsupporting
confidence: 91%
“…Similar mechanisms (i.e. those related to the proliferative effect of IGF-1) have been recently reported in the mouse chondrocyte ATDC5 cell line [14] and thus, based on those results as well as our data reported in this study, we propose the existence of a mechanism involving MAPK pathway that would regulate chondrocyte proliferation and transduce vanadate effect (Fig. 5A).…”
Section: Mapk Pathway Mediates Vanadate Stimulation Of Vsa13supporting
confidence: 92%
“…This inhibition was seen only when bones were stimulated to grow by the inclusion of pharmacological insulin concentrations in the culture medium. We (Phornphutkul et al, 2004) and others (Pandini et al, 2002) have demonstrated that the effects of high concentration insulin are likely to be mediated by IGF-I receptors and their downstream signaling pathways. In the fetal rat metatarsal explant model, similar growth was observed in bones exposed to 10 g/ml insulin or 10 nM of IGF-I.…”
Section: Discussionmentioning
confidence: 96%